A Historical Perspective of Landscape and Human Population Dynamics in Guimarães (Northern Portugal): Possible Implications of Rural Fire Risk in a Changing Environment - Nunes, Leonel (2022)
The occupation of a territory combines a set of variables which affect the development of the mode by which populations have been organized throughout history. How this occupation takes place demonstrates much of a territory’s past and shows how the populations managed to make the most out of the available resources. The region of Entre-Douro-e-Minho (Northern Portugal), similarly to what happens in other regions, such as Galicia (Northern Spain), Brittany (Northern France), or Ireland, presents a type of dispersed land use, with an alternation of urban, agriculture, and forest areas. On one hand, this proximity allows urban populations to come into contact with a rural environment. On the other hand, this proximity also causes a set of problems, namely those related to rural fires, which are now enhanced by climate change, and associated phenomena, such as heatwaves and the lack of precipitation. The present work analyzes the evolution of rural fires in 1975–2019, in the municipality of Guimarães (Northern Portugal), to understand how these events have been distributed over time and evolved in a climate change scenario. Based on the results and discussion presented, it can be concluded that there is an increasing trend in the occurrence of rural fires in the territory under study, and that this can also be associated to climate change, in the form of a gradual increment in temperature, particularly in the autumn months, and a decrease in rainfall. This situation is responsible for the increment of the risk caused by the proximity of the populations to forest and agricultural areas because rural fires can jeopardize the safety of people and goods.